2019
DOI: 10.1007/s11192-019-03115-x
|View full text |Cite
|
Sign up to set email alerts
|

Scientific production on mobile information literacy in higher education: a bibliometric analysis (2006–2017)

Abstract: This paper offers a bibliometric analysis of the scientific production on Mobile Information Literacy (m-IL) in Higher Education published between 2006 and 2017, taking into account papers covered by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 71 publications
1
20
0
2
Order By: Relevance
“…Furthermore, based on the background of big data, the Association of College and Research Libraries (ACRL) has used the concept of “data literacy” many times (Prado & Marzal, 2013 ). Pinto et al ( 2019 ), b ) adopted the concept of “mobile information literacy” for ubiquitous learning, connectivism, and multimodal learning. Thus, technology has always been an important factor in the development of information literacy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, based on the background of big data, the Association of College and Research Libraries (ACRL) has used the concept of “data literacy” many times (Prado & Marzal, 2013 ). Pinto et al ( 2019 ), b ) adopted the concept of “mobile information literacy” for ubiquitous learning, connectivism, and multimodal learning. Thus, technology has always been an important factor in the development of information literacy.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that all fields should collaborate in the future. Pinto et al ( 2019 ) offered a bibliometric analysis of the scientific production on Mobile Information Literacy in Higher Education published between 2006 and 2017. They note that incorporating IL in the context of online learning highlights how mobile technologies are gaining ground at all levels.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…List (2019) analyzed various aspects of student digital literacy development. A bibliometric analysis of scientific researches published during the period from 2006 to 2017 devoted to the study of literacy in the application of mobile information technologies in higher education was made by Pinto et al (2019). The researches to determine the relationship between socio-economic status indicators (SES) and ICT literacy among students are highly controversial (Hatlevik and Christophersen 2013; Hohlfeld et al 2013; Scherer and Siddiq 2019).…”
Section: Literature Reviewmentioning
confidence: 99%